Leadership in Action: Identity Crisis: Recognizing the Triggers of a Growing Type of Conflict - Ruderman, Marian; Chrobot-Mason, Donna; Weber, Todd (Center for Creative Leadership, 2007)
As today's organizations become more globally oriented, their leaders must help those they lead deal with an increasingly prevalent source of conflict-social identities. Our social identities are made up of the aspects of ourselves that are tied to the various demographic and cultural groups to which we belong. Learning how to deal with social identity conflicts isn't easy, but it is possible.
Keywords: Leadership